A Comparison of two prosthetic feet (SACH foot & Single axis foot) on Walking Balance Variables in Unilateral Transtibial Amputees. - sara Alavi; Reza Vahab Kashani; Masoud Karimlou; hassan Saeedi; Mahmoud Bahramizadeh (Afarand Scholarly Publishing Institute, 2010)
Abstract   Background and Purpose: The prosthetic foot is designed to replace many of the functions of the anatomic human foot.As the connection between the prosthesis and the ground is must mimic the biomechanical characteristics of the humanfoot as much as possible. One of the important functions of the ankle-foot complex is dynamic balance.   Objective: To compare the effectiveness of SACH and Single axis foot on dynamic balance variables.   Materials and Methods: A Randomized cross over study was designed on five transtibial amputees using a SACH foot and Single axis foot.Ten able bodied controls practicipated in this study too.Both of groups was tested using Computerized Dynamic Posturography.   Results : All of practicipated was female and adult with the average 26.3 years old and23.73Kg/m2body mass index.Comparison of two prosthetic feet worn by transtibial amputees did not show statistically significant different in Step Length, Step Width and Asymmetry of Step Length.But compared to NA controls, TT amputees had bigger step width while using Single Axis foot (p<0.05) and shorter Step Length while wearing SACH foot (p<0.05).   Conclusion: In transtibial amputees, SACH foot had better balance control in frontal plane and Single Axis foot prepared more balance control in sagital plane.   Key Word: SACH foot, Single Axis foot, Below knee prosthesis, Transtibial amputation.